Institutionalizing Sabar Ngantri as a Life Philosophy at Baitul Makmur Islamic Boarding School in a Generation Alpha Context - Wahyudin, Wahyudin; Wahyudi, Dedi (Program Studi Aqidah dan Filsafat Islam, 2025)
This study examines how SANTRI, an acronym for sabar ngantri, is enacted as a locally grounded life philosophy at Pondok Pesantren Baitul Makmur in Metro, Lampung, within the Generation Alpha context. The study addresses recurring tensions in crowded routines, including line cutting, pushing, verbal disputes, and difficulty sustaining discipline during shared activities. A qualitative field-based study with a descriptive orientation was conducted. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interpretive approach with thematic coding and triangulation across sources. The main informant was an ustazdah responsible for supervising daily routines, complemented by student perspectives representing varied experiences in the boarding environment. The findings indicate that SANTRI is reinforced as an ethical discipline across core routines such as submitting Qur’anic recitations and classical text readings, performing ablution, taking meals, bathing, and practicing respect rituals such as sungkem and sowan to the kiai. In this setting, SANTRI supports emotional regulation and fairness by translating moral instruction into observable turn-taking behavior reinforced by caregivers and peers. The study presents SANTRI as a locally grounded model of character education that helps reduce everyday conflict while supporting communal stability in a dense pesantren environment shaped by the fast-paced habits associated with digitally socialized youth.